The evolution of resource distribution, slow diffusion, and dispersal strategies in heterogeneous populations - Zahan, Ishrat; Kamrujjaman, Md.; Abdul Alim, Md.; Shahidul Islam, Md.; Khan, Taufiquar (Frontiers in Applied Mathematics and Statistics, 2023)
The diffusion in river-ocean ecology and for wild animals, including birds, mainly depends on available resources and habitats. This study explores the dynamics of the resource-based competition model for two interacting species to investigate the spatiotemporal effect in a spatially distributed heterogeneous environment with no-flux boundary conditions. The main focus of this study is based on diffusion strategy, where the carrying capacity of two competing species is considered unequal. Both species are contemplating the same growth function with different migration coefficients. The stability of global coexistence and quasi-trivial equilibrium are also studied in different conditions of resource function and carrying capacity. Furthermore, we investigate the case of competitive exclusion for various linear combinations of resource functions and carrying capacity. Additionally, we extend the study to the instance where a higher migration rate negatively impacts population growth in competition. The model's efficacy in the case of one and two space dimensions is also demonstrated using numerical study.